Synergistic antifungal interaction of N-(butylcarbamothioyl) benzamide and amphotericin B against Cryptococcus neoformans - Andriani, Gabriella Maria; Spoladori, Lais Fernanda de Almeida; Fabris, Marciéli; Camargo, Priscila Goes; Pereira, Patrícia Morais Lopes; Santos, Jussevania Pereira; Bartolomeu-Gonçalves, Guilherme; Alonso, Lais; Lancheros, Cesar Armando Contreras; Alonso, Antonio; Nakamura, Celso Vataru; Macedo, Fernando; et al. (Frontiers in Microbiology, 2023)
Cryptococcus neoformans is one of the leading causes of invasive fungal infections worldwide. Cryptococcal meningoencephalitis is the main challenge of antifungal therapy due to high morbidity and mortality rates, especially in low- and middle-income countries. This can be partly attributed to the lack of specific diagnosis, difficulty accessing treatment, antifungal resistance and antifungal toxicity. In the present study, the effect of the synthetic thiourea derivative N-(butylcarbamothioyl) benzamide (BTU-01), alone and combined with amphotericin B (AmB), was evaluated in planktonic and sessile (biofilm) cells of C. neoformans. BTU-01 alone exhibited a fungistatic activity with minimal inhibitory concentrations (MICs) ranging from 31.25 to 62.5 µg/mL for planktonic cells; and sessile MICs ranging from 125.0 to 1000.0 µg/mL. BTU- caused a concentration-dependent inhibitory activity of cryptococcal urease and did not interfere with plasma membrane fluidity. Molecular docking was performed on Canavalia ensiformis urease, and BTU-01 showed relevant interactions the enzyme. The combination of BTU-01 and AmB exhibited synergistic fungicidal activity against planktonic and sessile cells of C. neoformans. Microscopic analysis of C. neoformans treated with BTU-01, alone or combined with AmB, revealed a reduction in cell and capsule sizes, changes in the morphology of planktonic cells; a significant decrease in the number of cells within the biofilm; and absence of exopolymeric matrix surrounding the sessile cells. Neither hemolytic activity nor cytotoxicity to mammalian cells was detected for BTU-01, alone or combined with AmB, at concentrations that exhibited antifungal activity. BTU-01 also displayed drug-likeness properties. These results indicate the potential of BTU-01, for the development of new strategies for controlling C. neoformans infections.